MULTIMEDIA DESIGN TRAINING FOR HIGH SCHOOL TEACHERS IN TANGERANG SELATAN - Habyba, Anik Nur; Surjasa, Dadang; Farhan, Ahmad; Rambung, Richard Antonius; Krismantan, Thalia Putri; Rhamanda, Dinda (Jurnal Pengabdian Kepada Masyarakat, 2023)
The teaching and learning process is a process that involves teachers and students. Interaction must be two-way in transferring knowledge so that teaching materials can be understood and appropriately understood. Teachers must be prepared before giving subject matter and are expected to have exciting teaching materials that can be studied and accessed at any time. Learning multimedia training is needed for high school teachers in South Tangerang. The material provided is about making learning videos with Canva. The material on editing and posting files generated through Canva to Youtube will also be provided. The training activities have been going well. The training participants felt that this activity was helpful and exciting and supported their educator careers. Participants wanted the action to be held longer so that the material could be deepened better. Apart from that, the follow-up service program was also treated with other training materials. The next PkM team is expected to be more prepared to collaborate with teachers to make the class atmosphere and material more interesting for students.